The psychosocial determinants relationship with burnout among nurses in Pahang, Malaysia - Nor Firdous Mohamed (Tanjong Malim, 2021)
The psychosocial determinants relationship with burnout among nurses in Pahang, Malaysia by Nor Firdous Mohamed